Multidimensional mass spectrometry to characterize degradation products generated during MALDI of polystyrenes prepared by controlled radical polymerization techniques. Issue 20 (22nd July 2016) - Chendo, Christophe; Le, Dao; Phan, Trang N. T.; Gigmes, Didier; Charles, Laurence
ABSTRACT: An analytical workflow involving high resolution mass analysis, collision‐induced dissociation and ion mobility was implemented to structurally characterize polymeric by‐products detected in lieu of intact species when performing matrix‐assisted laser desorption/ionization (MALDI) of polystyrenes with fragile end groups. Studied samples were prepared by atom transfer radical polymerization, reversible addition–fragmentation transfer polymerization and nitroxide‐mediated polymerization. Spectral resolution enabled by orthogonal injection of MALDI ions into a reflectron time‐of‐flight mass analyzer allowed a thorough inventory of species, including some with the same nominal m/z value but different elemental composition. Individual end‐group mass determination was achieved in MS/MS experiments, implementing an additional separative dimension based on ion mobility prior to CID to assist precursor ion selection in case of interferences. Besides validating commonly reported polystyrene chains terminated with either endo‐ or exo‐double bond, this multidimensional approach permitted to show that initiating moiety could also be affected by the MALDI process. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 3388–3397 Abstract : High resolution mass spectrometry, accurate mass measurements, collision‐induced dissociation and ion mobility are combined for a detailed structural characterization of by‐products generated during MALDI of polystyrenes holding a labile end‐group.